Conversion therapy for advanced hepatocellular carcinoma in the era of precision medicine: Current status, challenges and opportunities - Wang, Ming‐Da; Xu, Xue‐Jun; Wang, Ke‐Chun; Diao, Yong‐Kang; Xu, Jia‐Hao; Gu, Li‐Hui; Yao, Lan‐Qing; Li, Chao; Lv, Guo‐Yue; Yang, Tian (Cancer science, 2024)
Hepatocellular carcinoma (HCC), the most prevalent malignancy of the digestive tract, is characterized by a high mortality rate and poor prognosis, primarily due to its initial diagnosis at an advanced stage that precludes any surgical intervention. Recent advancements in systemic therapies have significantly improved oncological outcomes for intermediate and advanced‐stage HCC, and the combination of locoregional and systemic therapies further facilitates tumor downstaging and increases the likelihood of surgical resectability for initially unresectable cases following conversion therapies. This shift toward high conversion rates with novel, multimodal treatment approaches has become a principal pathway for prolonged survival in patients with advanced HCC. However, the field of conversion therapy for HCC is marked by controversies, including the selection of potential surgical candidates, formulation of conversion therapy regimens, determination of optimal surgical timing, and application of adjuvant therapy post‐surgery. Addressing these challenges and refining clinical protocols and research in HCC conversion therapy is essential for setting the groundwork for future advancements in treatment strategies and clinical research. This narrative review comprehensively summarizes the current strategies and clinical experiences in conversion therapy for advanced‐stage HCC, emphasizing the unresolved issues and the path forward in the context of precision medicine. This work not only provides a comprehensive overview of the evolving landscape of treatment modalities for conversion therapy but also paves the way for future studies and innovations in this field. Setting a foundation for future research and advancements in HCC treatment, aligning with the emerging paradigm of precision medicine; addressing the need for a holistic approach in managing advanced‐stage HCC, and advocating for a balance between aggressive treatment and quality of life considerations.